2019
DOI: 10.1097/rti.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Half-dose Coronary Artery Calcium Scoring

Abstract: ASIR 70% coupled with reduction of tube current by 50% allowed for significant dose reduction and no detrimental effects on image quality, with minimal patient reclassification in nonobese patients. In obese patients, excessive noise may lead to a clinically significant reclassification rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…In addition, the mean BMI of our population was small. Increased image noise in obese patients influences the quantification of the Agatston score and leads to reclassification in the risk category (41). Finally, this is a single-center study and findings are limited to one CT vendor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mean BMI of our population was small. Increased image noise in obese patients influences the quantification of the Agatston score and leads to reclassification in the risk category (41). Finally, this is a single-center study and findings are limited to one CT vendor.…”
Section: Discussionmentioning
confidence: 99%
“…Caruso and colleagues 57 analyzed coronary artery calcium scoring protocols at SD (120 kVp, 170 mAs) reconstructed by FBP and at half dose (120 kVp, 85 mAs) reconstructed by ASiR at various strength levels. Results demonstrated that ASiR-70% showed higher SNR and CNR compared with FBP and that the half-dose protocol provided 52% less radiation dose without a significant impact on subjective analysis.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Nowadays, the IR algorithm has been introduced by all different vendors in CT scanners because it has the advantages of reducing artefacts and noise scanning at lower radiation dose [13,14]. These algorithms represent an extraordinary method to reduce radiation dose and preserving image quality, in particular for oncologic patients and cardiovascular imaging [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%